RANCANGAN PROGRAM PELAYANAN BIMBINGAN DAN KONSELING BERBASIS IDENTIFIKASI PERMASALAHAN PESERTA DIDIK - Jessy Zulpatri; Rahma Wira Nita; Rahmawati Wae (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem of students feeling shunned, lack of student participation in learning. The study aims to describe: student learning problems in the aspects of 1) personal, 2) social, 3) learning, 4) career, 5) design a service program based on identification of student problems at SMAN 1 Linggo Sari Baganti. As well as designing a program based on the analysis of problems faced by students. The type of research is descriptive quantitative. The population of this study were 355 students of SMAN 1 Linggo Sari Baganti. The sampling technique used a simple random sampling technique of 35 people. The instrument used was a questionnaire. Data analysis used a percentage technique. Based on the results of the study revealed that student problems in the fields of: 1) personal are in the moderate criteria 2) social are in the moderate criteria 3) learning are in the many criteria 4) career are in the many criteria 5) design of Guidance and Counseling Service Program. This information service focuses on time discipline and personal responsibility, wisely managing desires and finances, increasing motivation and enthusiasm for learning, and independence in decision-making. Based on the results of this study, it is recommended that guidance and counseling teachers implement the program designed through this research.